2018
DOI: 10.1093/ageing/afy169
|View full text |Cite|
|
Sign up to set email alerts
|

Sarcopenia: revised European consensus on definition and diagnosis

Abstract: Background In 2010, the European Working Group on Sarcopenia in Older People (EWGSOP) published a sarcopenia definition that aimed to foster advances in identifying and caring for people with sarcopenia. In early 2018, the Working Group met again (EWGSOP2) to update the original definition in order to reflect scientific and clinical evidence that has built over the last decade. This paper presents our updated findings. Objectives To increase consistency of research design, clinical diagnoses, and ultimately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

130
9,589
23
612

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 8,792 publications
(10,354 citation statements)
references
References 151 publications
130
9,589
23
612
Order By: Relevance
“…Although gait speed is related to skeletal muscle mass as a predictor of sarcopenia [34], the present study found no significant differences between the BMI groups in 10MGT for men, despite significant differences in muscle strength. In the present study, 10MGT was measured at maximum speed.…”
Section: Discussioncontrasting
confidence: 86%
“…Although gait speed is related to skeletal muscle mass as a predictor of sarcopenia [34], the present study found no significant differences between the BMI groups in 10MGT for men, despite significant differences in muscle strength. In the present study, 10MGT was measured at maximum speed.…”
Section: Discussioncontrasting
confidence: 86%
“…Recently, it has been hypothesized that contracting skeletal muscles contribute to brain preservation by the secretion of neurotrophic factors. 49 The EWGSOP2 considers low muscle strength as a key characteristic of sarcopenia, considering the age-related changes of skeletal muscle and availability of measurements in various settings. Since skeletal muscle has a role in metabolic processes, sarcopenia could also adversely affect mental function via metabolic and endocrine mechanisms.…”
Section: Sarcopenic Obesity As a Potential Risk Factor For Depressionmentioning
confidence: 99%
“…Diagnosis of sarcopenia was based on definitions from the European Working Group on Sarcopenia in Older People (EWGSOP2) in 2018 . According to these criteria, probable sarcopenia was defined as low muscle strength.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum grip strength was recorded. The cutoff thresholds for handgrip strength were accepted against sex as recommended (27 kg for males and 16 kg for females) …”
Section: Methodsmentioning
confidence: 99%